Deposition rate effect on microstructure and perpendicular magnetic anisotropy of iron films prepared by ion-beam-assisted deposition. (October 2019) - Lyadov, N.M.; Vagizov, F.G.; Vakhitov, I.R.; Gumarov, A.I.; Ibragimov, Sh.Z.; Kuzina, D.M.; Faizrakhmanov, I.A.; Khaibullin, R.I.; Shustov, V.A.
Abstract: Thin films of iron with different thickness (⁓40–300 nm) were deposited on quartz and silicon substrates by using ion beam assisted deposition (IBAD) technique. The influence of film thickness and deposition rate on microstructure, magnetic phase composition and perpendicular magnetic anisotropy (PMA) of iron films were studied by electron microscopy, X-ray diffraction, Mössbauer spectroscopy, vibrating-sample magnetometry and differential thermomagnetic analysis. Shown, that phase composition and magnetic properties of films depend substantially on the deposition rate, and, in fact, don't depend on both film thickness and the type of substrate. The strong PMA is observed in iron films formed at low ( 3 nm/min) and medium ( 10 nm/min) deposition rates only. The microstructure is characterized by the presence of nanocrystalline grains of α-Fe phase, as well as a significant fraction of disordered iron phase and nonmagnetic oxide phase of FeO (up to 20%). The FeO phase occurs due to the reaction of iron atoms with the residual atmosphere of the vacuum chamber. Moreover, significant positive deformation (about 3%) of crystal lattice of α-Fe grains was observed. The effect of deposition rate on the crystallinity, phase composition and PMA in thin iron films we associate with the features of the IBAD process. Highlights: Deposition rate effect on the perpendicular magnetic anisotropy (PMA) of the Fe films was studied. The PMA value does not depend on the type of substrate and thickness of the Fe film. The elemental-phase composition of the iron films significantly depends on deposition rate. Correlation between FeO content and PMA was established. DTMA data indicates a non-uniform magnetic-phase composition of the iron films with PMA.